Maintenance of Consent Paper in Daily Dental Practices - Binte Islam, Nabhira Aftabi; Shahrin, Sharika; Hamdullah, Md (Journal of Preventive and Social Medicine, 2022)
Background: To assess maintenance of consent paper in daily dental practices. Methods: It was a cross-sectional study. To assess maintenance of consent paper in daily dental practice at the chambers of the dentist. Data were collected through face to face interview. Dental chambers were selected by simple random sampling technique and respondents were selected purposively in Mymensingh sadar. 50 chambers and 70 dental surgeons were interviewed. Study period was January to March, 2019. Results: In respect of distribution of the chamber owners by sex, female owners comprised 16% and 84% was male owners. By educational background of chamber owners, 40% owners had no B.D.S degree. It was found that 16% dental chambers had two dental surgeons and 84% dental chambers had one dental surgeon. Of all, 92.90% dental surgeons had knowledge about consent paper. The study showed that 80% dental surgeon sometimes, 7.1% dental surgeon always maintained consent paper in daily practice. Among the dental surgeons, 44.3% sometimes faced problem for taking consent paper in daily practice. Among all, 71.4% maintained verbal consent, 7.1% written and 21.4% maintained implied consent. Of all, 94. 3% dental surgeons maintained written consent paper only for costly treatment and specialized cases while 18.6% thought that it was not important and 40% thought that time consuming and 34.3% thought that patients were not interested. It was also found that 42% ancillary of the dental chambers had diploma degree and 58% had no degree. Conclusion: It is a general legal and ethical principle that one must get valid consent because it is the patients' rights before starting treatment or physical investigation. JOPSOM 2021; 40(1): 22-25